Pengaruh Brand Image, Kualitas Produk dan Store Atmosphere terhadap Keputusan Pembelian Produk: Survei pada Customer Kedai Kopi Janji Jiwa Di Manahan, Surakarta - Dwi Suryadi; Sumaryanto Sumaryanto; Setyaningsih SU (Pusat Riset dan Inovasi Nasional, 2026)
Kopi Janji Jiwa is one of the local coffee brands that has successfully won a prestigious award from Top Brand. The formulation of the problem in this study is whether brand image, product quality and store atmosphere have a significant effect on product purchasing decisions at Kedai Kopi Janji Jiwa Manahan Solo. The purpose of this study is to analyze the significance of the influence of brand image, product quality and store atmosphere on product purchasing decisions at Kedai Kopi Janji Jiwa Manahan Solo.This study uses a survey method conducted on consumers of Janji Jiwa Manahan Solo Coffee Shop. Data collection in this study used a questionnaire distributed to respondents. The population in this study were all consumers of Janji Jiwa Manahan Solo Coffee Shop. whose number is unknown. Sampling in this study used a accidental sampling method with a sample size of 100 respondents. The study used instrument testing and classical assumption testing. The data analysis technique used in this study used descriptive analysis, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R2).The results of the statistical test show that the instrument test for all variables is valid and reliable. The results of the classical assumption test show that all variables pass the classical assumption test. The results of this study obtained a regression equation, namely Y = 2.750 - 0.646 X1 + 1.128 X2 + 0.157 X3. The results of the t test show that the variables brand image, product quality and store atmosphere have a significant effect on purchasing decisions at Janji Jiwa Manahan Solo Coffee Shop. The results of the F test show that the model used to test the effect of brand image, product quality and store atmosphere variables on purchasing decisions is correct. The results of the determination coefficient (R2) = 90.5%. The rest (100% - 90.5%) = 9.5% is explained by other variables outside the model, such as price, product quality, and product innovation